2020
DOI: 10.1101/2020.02.22.960963
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Instability of aquaglyceroporin (AQP) 2 contributes to drug resistance inTrypanosoma brucei

Abstract: 34Defining mode of action is vital for both developing new drugs and predicting 35 potential resistance mechanisms. African trypanosome pentamidine and 36 melarsoprol sensitivity is predominantly mediated by aquaglyceroporin 2 (TbAQP2), a 37 channel associated with water/glycerol transport. TbAQP2 is expressed at the flagellar 38 pocket membrane and chimerisation with TbAQP3 renders parasites resistant to both 39 drugs. Two models for how TbAQP2 mediates pentamidine sensitivity have emerged; 40 that TbAQP2 med… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Trypanosoma brucei AQP1 and AQP3 display the internal arrangements in the protein pore observed in canonical AQPs, including the canonical ‘NPA’ within two half α -helices and a narrower ‘aromatic/arginine’ (ar/R) motif (Beitz, 2005). Interestingly, TbAQP2 does not retain this canonical configuration, displaying an unconventional ‘NPS/NSA’ filter motif and rearrangement in the ar/R motif that is replaced by a neutral leucine at position 264 (L264), followed by aliphatic, rather than aromatic, residues (A88, I110, V249 and L258), which are equivalent to the ‘IVLL’ motif observed in the selectivity pore of canonical AQPs (de Groot and Grubmuller, 2001; Baker et al ., 2013; Quintana et al ., 2020). These structural features indicate that TbAQP2 can accommodate larger solutes through the selectivity pore (Uzcategui et al ., 2004).…”
Section: Evolution Functions and Roles In Protistsmentioning
confidence: 99%
See 4 more Smart Citations
“…Trypanosoma brucei AQP1 and AQP3 display the internal arrangements in the protein pore observed in canonical AQPs, including the canonical ‘NPA’ within two half α -helices and a narrower ‘aromatic/arginine’ (ar/R) motif (Beitz, 2005). Interestingly, TbAQP2 does not retain this canonical configuration, displaying an unconventional ‘NPS/NSA’ filter motif and rearrangement in the ar/R motif that is replaced by a neutral leucine at position 264 (L264), followed by aliphatic, rather than aromatic, residues (A88, I110, V249 and L258), which are equivalent to the ‘IVLL’ motif observed in the selectivity pore of canonical AQPs (de Groot and Grubmuller, 2001; Baker et al ., 2013; Quintana et al ., 2020). These structural features indicate that TbAQP2 can accommodate larger solutes through the selectivity pore (Uzcategui et al ., 2004).…”
Section: Evolution Functions and Roles In Protistsmentioning
confidence: 99%
“…Further biochemical and genetic manipulation studies demonstrated that deletion of AQP2, but not AQP3, led to a significant increase in the EC 50 of both compounds, mirroring the behaviour observed in previously generated laboratory strains and field isolates (Munday et al ., 2014; Graf et al ., 2015 b ; Song et al ., 2016). Other observations such as localization to the flagellar pocket in the bloodstream form (Munday et al ., 2014; Graf et al ., 2015 b ; Song et al ., 2016; Quintana et al ., 2020), as well as the unusual pore structure discussed above, led to the hypothesis that pentamidine and melarsoprol are likely to interact with high affinity to AQP2 located in the flagellar pocket (Alghamdi et al ., 2020), posing the question of how these compounds are internalized and also the mechanisms for resistance.…”
Section: Tbaqp2 and Multidrug Resistancementioning
confidence: 99%
See 3 more Smart Citations